RcaE-Dependent Regulation of Carboxysome Structural Proteins Has a Central Role in Environmental Determination of Carboxysome Morphology and Abundance in Fremyella diplosiphon - Brandon A. Rohnke (American Society for Microbiology, 2018)
ABSTRACT Carboxysomes are central to the carbon dioxide-concentrating mechanism (CCM) and carbon fixation in cyanobacteria. Although the structure is well understood, roles of environmental cues in the synthesis, positioning, and functional tuning of carboxysomes have not been systematically studied. Fremyella diplosiphon is a model cyanobacterium for assessing impacts of environmental light cues on photosynthetic pigmentation and tuning of photosynthetic efficiency during complementary chromatic acclimation (CCA), which is controlled by the photoreceptor RcaE. Given the central role of carboxysomes in photosynthesis, we investigated roles of light-dependent RcaE signaling in carboxysome structure and function. A ΔrcaE mutant exhibits altered carboxysome size and number, ccm gene expression, and carboxysome protein accumulation relative to the wild-type (WT) strain. Several Ccm proteins, including carboxysome shell proteins and core-nucleating factors, overaccumulate in ΔrcaE cells relative to WT cells. Additionally, levels of carboxysome cargo RuBisCO in the ΔrcaE mutant are lower than or unchanged from those in the WT strain. This shift in the ratios of carboxysome shell and nucleating components to the carboxysome cargo appears to drive carboxysome morphology and abundance dynamics. Carboxysomes are also occasionally mislocalized spatially to the periphery of spherical mutants within thylakoid membranes, suggesting that carboxysome positioning is impacted by cell shape. The RcaE photoreceptor links perception of external light cues to regulating carboxysome structure and function and, thus, to the cellular capacity for carbon fixation. IMPORTANCE Carboxysomes are proteinaceous subcellular compartments, or bacterial organelles, found in cyanobacteria that consist of a protein shell surrounding a core primarily composed of the enzyme ribulose-1,5-biphosphate carboxylase/oxygenase (RuBisCO) that is central to the carbon dioxide-concentrating mechanism (CCM) and carbon fixation. Whereas significant insights have been gained regarding the structure and synthesis of carboxysomes, limited attention has been given to how their size, abundance, and protein composition are regulated to ensure optimal carbon fixation in dynamic environments. Given the centrality of carboxysomes in photosynthesis, we provide an analysis of the role of a photoreceptor, RcaE, which functions in matching photosynthetic pigmentation to the external environment during complementary chromatic acclimation and thereby optimizing photosynthetic efficiency, in regulating carboxysome dynamics. Our data highlight a role for RcaE in perceiving external light cues and regulating carboxysome structure and function and, thus, in the cellular capacity for carbon fixation and organismal fitness.